Green synthesis of silver nanoparticles using Pyrostegia venusta extract, characterization and estimation of antioxidant, antiglycation and anti-aging activities - Regildo Márcio Gonçalves da Silva; Pedro Augusto Pereira Rosatto; Isabelly do Nascimento Pereira; Laura Camargo Zibordi; Hugo Henrique Santos; Filipe Oliveira Granero; Célia Cristina Malaguti Figueiredo; Patrícia Soares Santiago; Carlos Augusto Prata Gaona; Nilson Nicolau-Junior; Luciana Pereira Silva (Journal of Genetic Engineering and Biotechnology)
Pyrostegia venusta presents phytoconstituents with biological properties including antioxidant activity. This study aimed to prepare P. venusta aqueous extract (PvAE), synthesize silver nanoparticles (AgNPs) through green synthesis using PvAE, determine their phytoconstituents, evaluate their in vitro antioxidants, antiglycation, and anti-aging activities, and analyze in silico docking of the main phenolic compounds. Phytoconstituents were identified by HPLC and determined by total polyphenols and flavonoids. AgNPs were characterized by scanning transmission electron microscopy and dynamic light scattering. Evaluation of antioxidant potential was performed by DPPH radical scavenging, FRAP, TBARS, ORAC, and oxidative hemolysis analysis. Evaluation of antiglycation activity was carried out by the determination of free amino groups, inhibition of AGEs formation, and REM assays. Anti-aging pandal was evaluated by in vitro and in silico assays. PvAE exhibited the highest total polyphenols (325.78 mg gallic acid equivalent g−1), while AgNPs showed the highest total flavonoids (373.53 mg rutin equivalent g−1). PvAE presented the highest antioxidant activity in DPPH test (74.90 %), although AgNPs exhibited antioxidant activity in ORAC, FRAP (862 μM Trolox equivalent g−1), TBARS (53.97 % inhibition of TBARS formation), and oxidative hemolysis inhibition (85.36 %) assays. Antiglycation evaluation demonstrated the activity of PvAE and AgNPs. PvAE presented in vitro enzymes inhibition and in silico studies demonstrated possible active binding sites between P. venusta main compounds and enzymes that may be correlated with their potential to act at pre- and post-transcriptional levels. Therefore, this study provides information regarding P. venusta and demonstrates that further studies are needed to evaluate its application.